Relative incidence of quarantine insect pest, Sternochetus mangiferae (Coleoptera : Curculionidae) on varieties and new hybrids of mango - REDDY, D SRINIVASA (The Indian Journal of Agricultural Sciences, 2015)
Studies on the incidence of mango stone weevil, Sternochetus mangiferae (Fabricius) on 18 varieties and 16 hybrids (released and pre-released) were conducted for three years during 2010-2012. Results revealed that all the varieties and hybrids both released and pre-released were susceptible to weevil attack. In varieties high incidence was recorded in Banglora (60.28%), followed by Kesar (48.46%), Manoranjan (42.78%) and Safeda (40.97%). The other commercial varieties, viz. Neelum (37.85%) had higher infestation compared to Baneshan (7.12%). Among all the varieities screened lowest percent infestation was observed in Khader (2.22) and Peterpasand (3.00). Produtur Avakai, Alipasand and Pulihora which were used for pickle purpose also had higher infestation ranging from (30.56-35.71%). In the hybrids Dasheri × Vikarabad shown maximum infestation (73.61%), followed by Padiri × Ambalavi (59.58%). Ratna had lowest infestation of 0.77% compared to Amrapali (43.14%), Mallika (20.56%) and Neeleshan (14.64%).